CoStar: a verified ALL(*) parser. - Lasser, Sam.; Casinghino, Chris.; Fisher, Kathleen.; Roux, Cody. (Tufts University. Tisch Library., 2023)
Keywords: interactive theorem proving, parsing.; Topic: Software and its engineering / Software creation and management / Software verification and validation / Formal software verification; Topic: Software and its engineering / Software notations and tools / Compilers / Parsers; ACM Open.